IADC/SPE Asia Pacific Drilling Technology Conference and Exhibition 2010
DOI: 10.2118/135670-ms
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Reach and Selectivity of Completions in Extended Reach Horizontal Wells

Abstract: Over 15 years of production and injection history within the Al Shaheen Field has provided more details on the reservoir heterogeneities and performance of extended reach horizontal wells. This additional data, along with the lateral extent of the reservoirs, has increased the need for longer and more selective horizontal completions. Three primary reservoirs have been developed to date and have different requirements regarding liners and completions. The commonality of all reservoirs is the requirement for lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…If the acid flux becomes too low to efficiently propagate wormholes in the formation, face dissolution of the wellbore, resulting in wellbore enlargement, will occur. Caliper logs run after acid jetting treatments in Qatar (Ritchie et al, 2010) indicate that significant wellbore enlargement did occur as shown in Fig. 4.6.…”
Section: Fig 42 -Wormhole Length At the Toe Segment As Function Of Timementioning
confidence: 91%
See 2 more Smart Citations
“…If the acid flux becomes too low to efficiently propagate wormholes in the formation, face dissolution of the wellbore, resulting in wellbore enlargement, will occur. Caliper logs run after acid jetting treatments in Qatar (Ritchie et al, 2010) indicate that significant wellbore enlargement did occur as shown in Fig. 4.6.…”
Section: Fig 42 -Wormhole Length At the Toe Segment As Function Of Timementioning
confidence: 91%
“…For the ultra-long horizontal well, the efficient placement of conventional acids is critical. The difficulty of applying acid (HCl) in long horizontal wells to uniformly remove drilling damage has been identified by several authors (Brink et al 2010;Hoch et al 2010;Ritchie et al 2010). In the long horizontal well completion type, due to the limitation of Coiled Tubing (CT), acid diversion, or foam technology application, Controlled Acid Jetting (CAJ) and Acid Jetting methods are considered as the effective solution to stimulate the well.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation